Clinical Outcomes of “U” Route Transforaminal Percutaneous Endoscopic Lumbar Discectomy in Chronic Pain Patients with Lumbar Spinal Stenosis Combined with Disc Herniation - Binbin Wu; Xinyi Tian; Ce Shi; Chenchen Jiang; Jing Zhang; Gonghao Zhan; Danli Xie (Pain Research and Management)
Introduction. “U” route transforaminal percutaneous endoscopic lumbar discectomy (PELD) was introduced for lumbar spinal stenosis (LSS) combined with disc herniation (DH) treatment. This study aims to explore the efficacy and safety of “U” route PELD on chronic pain patients with LSS combined with DH. Methods. Degenerative LSS combined with DH patients who underwent “U” route PELD were reexamined, and 80 patients were recruited and followed up for 2 years. The other 80 healthy individuals who were age- and sex-matched to the patients without chronic pain were enrolled as healthy controls. Minimum dura sac cross-sectional area (mDCSA) by MRI, Visual Analog Scale (VAS), Oswestry Disability Index (ODI), and modified MacNab outcomes were assessed. Emotional evaluation of pain catastrophizing and depression was documented with Pain Catastrophizing Scale (PCS) and Beck Depression Inventory (BDI), respectively, for patients before and after surgery and healthy individuals. Results . All patients were of the age range from 47 to 85 years, with an average of 59.5 ± 9.76 years. Symptoms duration was 114.6 ± 22.77 months, operation time was 87.7 ± 25.20 minutes, and the average hospital stay was 5.8 ± 2.81 days. Four patients quit, and hence, a total of 76 patients completed the follow-up. The results indicated that mDCSA was improved significantly after operation (p<0.001), either low back and leg VAS or ODI decreased over time (p<0.001), and the excellent-to-good rate was improved from 88.75% to 93.42% during postoperative 2 years (p<0.05). Complications of dural tear, nerve root, or dysesthesia were reported in 5 patients, and all recovered after conservative therapy. The scores of pain catastrophizing were reduced after operation (p<0.001), but no significance of BDI was found between patients and healthy controls (p>0.05). Conclusions. The “U” route PELD seems an alternative to LSS combined with DH treatment, which might reach a better decompression and effectively improve chronic pain conditions. Still, the complications were potential and required further consideration.